Antimicrobial activity of leucine‐substituted decoralin analogs with lower hemolytic activity. (10th August 2017) - Torres, Marcelo Der Torossian; Pedron, Cibele Nicolaski; da Silva Lima, Julia Aparecida; da Silva, Pedro Ismael; da Silva, Fernanda Dias; Oliveira, Vani Xavier
Abstract : Linear cationic α‐helical antimicrobial peptides are promising chemotherapeutics. Most of them act by different mechanisms, making it difficult to microorganisms acquiring resistance. Decoralin is an example of antimicrobial peptide; it was described by Konno et al. and presented activity against microorganisms, but with pronounced hemolytic activity. We synthesized leucine‐substituted decoralin analogs designed based on important physicochemical properties, which depend on the maintenance of the amphiphilic α‐helical tendency of the native molecule. Peptides were synthesized, purified, and characterized, and the conformational studies were performed. The results indicated that the analogs presented both higher therapeutic indexes, but with antagonistic behavior. While [Leu] 10 ‐Dec‐NH2 analog showed similar activity against different microorganisms (c.a. 0.4–0.8 μmol L −1 ), helical structuration, and some hemolytic activity, [Leu] 8 ‐Dec‐NH2 analog did not tend to helical structure and presented antimicrobial activities two orders higher than the other two peptides analyzed. On the other hand, this analog showed to be the less hemolytic (MHC value = 50.0 μmol L −1 ). This approach provided insight for understanding the effects of the leucine substitution in the amphiphilic balance. They led to changes on the conformational tendency, which showed to be important for the mechanism of action and affecting antimicrobial and hemolytic activities. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Two leucine decoralin analogs were synthesized in view of the possible effects of the physicochemical properties of this residue on the amphiphilic α‐helical tendency of the native molecule. The results indicated that the analogs presented both higher therapeutic indexes, but with antagonistic behavior. [Leu] 10 ‐Dec‐NH2 analog showed activity against the microorganisms, helical structuration, and some hemolytic activity, like decoralin. Otherwise, [Leu] 8 ‐Dec‐NH2 analog did not tend to helical conformation and presented antimicrobial activities two orders higher than the other two peptides described with the lowest hemolytic activity.